2010
DOI: 10.1177/0891988710392375
|View full text |Cite
|
Sign up to set email alerts
|

Association of Frontal Subcortical Circuits Infarcts in Poststroke Depression: A Magnetic Resonance Imaging Study of 591 Chinese Patients With Ischemic Stroke

Abstract: Despite extensive research into poststroke depression (PSD), the role played by lesion location in the pathogenesis of PSD remains uncertain. The aim of this study was to estimate the magnetic resonance imaging (MRI) correlates of PSD in Chinese patients with first or recurrent stroke. A total of 591 patients with acute ischemic stroke admitted to the acute stroke unit of a university-affiliated regional hospital in Hong Kong were recruited. A psychiatrist assessed all the patients 3 months after the stroke. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 27 publications
4
23
0
1
Order By: Relevance
“…The lack of consensus about the relationship between lesion locations and PSD might be due to different study methodology, including the source of study populations, timing of first interview after stroke, and measurement of depression [11]. A number of recent studies have demonstrated that patients with lesions in the frontal lobe had a higher risk of PSD and have provided some pathophysiological underpinnings for PSD [12], [13]. Whether frontal lobe lesions are associated with the course of PSD is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…The lack of consensus about the relationship between lesion locations and PSD might be due to different study methodology, including the source of study populations, timing of first interview after stroke, and measurement of depression [11]. A number of recent studies have demonstrated that patients with lesions in the frontal lobe had a higher risk of PSD and have provided some pathophysiological underpinnings for PSD [12], [13]. Whether frontal lobe lesions are associated with the course of PSD is still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…MRI studies reveal that major depressive disorder may involve pathological changes of the temporal and frontal lobes, including the superior temporal gyrus, the hippocampus, the amygdala, the anterior cingulate gyrus, and the orbitofrontal area [22] . Involvement of the frontal lobe and infarcts on frontal subcortical circuits are also an independent predictor of the development of post-stroke depression [23][24][25] . Medial pre-frontal networks that are connected to the medial pre-frontal cortex and the medial as well as the caudo-lateral orbital cortex are involved in the neural networks related to depressive episodes [26] .…”
Section: Discussionmentioning
confidence: 99%
“…Az egyik leggyakrabban vizsgált és sokat vitatott kér-dés a PSD és az agyi károsodás lokalizációja közötti összefüggés. Ugyanazon munkacsoport a bal frontális pólushoz való közelség, illetve a jobb occipitalis laesio és a depresszió összefüggését hangsúlyozta [24,33], megint mások egyéb anatómiai képletek károsodásával állítják párhuzamba a depresszió előfordulását [30,34]. A legtöbb vizsgálat azonban nem talált szignifi káns kapcsolatot a károsodott agyi terület oldallokalizációja és anteroposterior elhelyezkedése között [35,36].…”
Section: A Psd Patomechanizmusaunclassified